Assisting the Treasurer of Public Works and Public Housing of East Tanjung Jabung to prepare an official travel report - Sulastri, Sulastri; Abidin, Zaenal; Wandi, Wandi; Yatima, Khusnul (Zabags International Journal of Engagement, 2024)
This research aims to improve the effectiveness and efficiency of the preparation of official travel reports at the Public Works and Public Housing Office of East Tanjung Jabung Regency, by providing assistance in the form of training and standard templates. The research method used is a qualitative approach with case studies, which involves in-depth interviews, observations, and documentation related to the preparation of official travel reports. Employees involved in reporting undergo training on the use of templates and administrative guidelines designed to make it easier to record and fill in data more accurately. The results showed that the assistance program successfully reduced the time to prepare reports from three days to one to two days, as well as improved the accuracy of reports by reducing administrative errors by up to 50%. Employees also showed an increase in confidence and motivation after the training, which had a positive impact on the quality of financial reporting. This study recommends the implementation of continuous training programs in government agencies to increase financial administration capacity, as well as the need for management support in the provision of administrative tools. These findings can serve as a model for capacity building for other government agencies to overcome similar administrative challenges